The Reality of Applying Institutional Self-evaluation Standards in Educational Departments in the Directorate of Education in Qalyubia Governorate “From the Point of View of its Employees” - Mujahid, Salem Saeed Shalabi (The Arab Journal of Administration, 2024)
The study aimed to clarify the intellectual foundations on which institutional self-evaluation is based, and to reveal the extent to which institutional self-evaluation standards are available in the educational departments of the Directorate of Education in Qalyubia Governorate, in addition to presenting proposals for developing the fulfillment of institutional self-evaluation standards in those departments. The study used the descriptive approach and reached several results, the most prominent of which are: the availability of institutional self-evaluation standards in the educational departments of the Directorate of Education in Qalyubia Governorate with a high degree of its twelve standards. The study also presented a number of proposals for developing the fulfillment of institutional self-evaluation standards; The most prominent of which are: directing and strengthening efforts in accordance with Egypt’s Vision 2030, managing the transition from paper transactions to electronic transactions with beneficiaries, and identifying and responding to the current needs and future expectations of beneficiaries.